An update on the biologics for the treatment of antiphospholipid syndrome - Yun, Zelin; Duan, Lizhi; Liu, Xiangjun; Cai, Qingmeng; Li, Chun (Frontiers in Immunology, 2023)
Antiphospholipid syndrome (APS) is a systemic autoimmune disease characterized by thrombosis and pregnancy morbidity with the persistent presence of antiphospholipid antibodies (aPLs). Although anticoagulation is the primary treatment for APS, it fails in approximately 20-30% of obstetric APS cases and more than 30% of thrombotic APS cases. Therefore, there is a need for new, targeted treatments beyond anticoagulants. Biologics, such as rituximab and eculizumab, have been recommended for refractory catastrophic APS. This review focuses on the recent advancements in the pathogenesis of APS and explores the potential of targeted treatments, including eculizumab, rituximab, belimumab, daratumumab, obinutuzumab, and anti-TNF-α antibodies, for APS management.